2017
DOI: 10.1016/j.rmcr.2017.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Pneumothorax caused by cystic and nodular lung metastases from a malignant uterine perivascular epithelioid cell tumor (PEComa)

Abstract: Perivascular epithelioid cell tumors (PEComas) are mesenchymal neoplasms with immunoreactivity for both melanocytic and smooth muscle markers. PEComas occur at multiple sites, and malignant PEComas can undergo metastasis, recurrence and aggressive clinical courses. Although the lung is a common metastatic site of PEComas, they usually appear as multiple nodules but rarely become cystic or cavitary. Here, we describe a female patient whose lungs manifested multiple cystic, cavity-like and nodular metastases 3 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 17 publications
0
9
0
1
Order By: Relevance
“…After emergency treatment of coagulopathy, an abdominal- pelvic CT scan detected an apparently large uterine fibroid and an endometrial biopsy revealed an uterine PEComa. A 44-year-old woman presented with pneumothorax due to lung metastases from a malignant uterine PEComa ( Okamoto et al, 2017 ).…”
Section: Gynecologic Pecomamentioning
confidence: 99%
“…After emergency treatment of coagulopathy, an abdominal- pelvic CT scan detected an apparently large uterine fibroid and an endometrial biopsy revealed an uterine PEComa. A 44-year-old woman presented with pneumothorax due to lung metastases from a malignant uterine PEComa ( Okamoto et al, 2017 ).…”
Section: Gynecologic Pecomamentioning
confidence: 99%
“…Metastases are most commonly described in the lungs -cases of pneumothorax caused by tumour infiltration [37], and in the liver and bones. Metastases to the extraperitoneal space have also been described as well as the central nervous system, ovary, adrenal glands, peritoneum, intestinal wall, skin, stomach, and lymph nodes [3,4,35,37,38]. For this reason, the diagnosis of malignant PEComa requires a complete evaluation of the staging as in the case of other sarcomas [39].…”
Section: Diagnosismentioning
confidence: 99%
“…*Correspondence: shoheijapan@jikei.ac.jp 1 Division of Thoracic Surgery, Department of Surgery, The Jikei University School of Medicine, 3-25-8 Nishishinbashi, Minatoku, Tokyo 105-0003, Japan Full list of author information is available at the end of the article treatment for metastatic recurrences of PEComas after primary lesion resection has not been established; however, radical resection of lung metastases associated with postoperative recurrence after the first radical resection of PEComas has been reported [4][5][6][7][8]. We report a patient who underwent complete surgical resection via left upper and right lower lobectomy involving a two-step procedure for bilateral lung metastases detected 8 years after undergoing radical surgery for a PEComa in the colon.…”
Section: Open Accessmentioning
confidence: 99%
“…Although the natural course of PEComas is not elucidated well, PEComas have malignant potential, and cases of distant metastasis have been reported [ 2 , 3 ]. The treatment for metastatic recurrences of PEComas after primary lesion resection has not been established; however, radical resection of lung metastases associated with postoperative recurrence after the first radical resection of PEComas has been reported [ 4 – 8 ]. We report a patient who underwent complete surgical resection via left upper and right lower lobectomy involving a two-step procedure for bilateral lung metastases detected 8 years after undergoing radical surgery for a PEComa in the colon.…”
Section: Introductionmentioning
confidence: 99%